ANALYZING FREEDOM OF EXPRESSION AND MEDIA SPEECH THROUGH CONSTITUTIONAL PERSPECTIVE OF INDIA - Nahak, Duryodhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Freedom of speech and expression, guaranteed under Article 19(1)(a) of the Indian Constitution, serves as a foundational right essential for democratic governance. While the Constitution ensures these freedoms, it also imposes reasonable restrictions to maintain public order, security, and sovereignty. The media, often referred to as the "fourth estate," plays a crucial role in promoting public discourse, holding governments accountable, and fostering democratic ideals. This paper explores the evolution of press freedom in India, key Supreme Court rulings, and the legal frameworks governing media operations. The research underscores the delicate balance between freedom and regulation, emphasizing the need to protect democratic values while ensuring accountability. Ultimately, the paper argues that a free and independent press is essential for sustaining transparency, facilitating informed public participation, and strengthening the democratic process in India.